Adoption and diffusion of improved technologies and production practices in agriculture: Insights from a donor-led intervention in Nepal - Kumar, Anjani; Takeshima, Hiroyuki; Adhikari, Naveen; Thapa, Ganesh; Joshi, Pramod Kumar; Karkee, Madhab (International Food Policy Research Institute, 2018)
Adoptions of improved technologies and production practices are important drivers of agricultural development in low-income countries like Nepal. There are still knowledge gaps concerning what determines the adoption of different types of technologies and practices, how information about them is diffused, and what general impacts the interventions promoting them are having. In this paper we partly close the gap, using data collected for evaluations of the Knowledge-Based Integrated Sustainable Agriculture in Nepal (KISAN) project led by USAID. We find that factors important to increasing the adoption of improved technologies and practices include improved access to markets, the role of the private sector in selling improved seeds and disseminating information, membership in progressive farmers’ groups and cooperative societies, participation in agricultural training and farm visits, the provision of subsidies for seeds, and access to credit. Different factors are also found to affect the sources that farmers use for gathering information before adoption. The effects of KISAN projects vary significantly across the different crops grown, based on the evaluation models that address self-selection of both project participation and crop choices.